Investigation of the characteristics of medication errors and adverse drug reactions using pharmacovigilance data in China - Xiaofang Tan; Dongshi Gu; Xiaowen Lin; Huan Fang; Tetsuya Asakawa (Elsevier, 2020)
The aim of this study was to investigate the characteristics of medication errors (MEs) and adverse drug reactions (ADRs) using data from the spontaneous reporting system, which is helpful to understand the actual situation of MEs in China. Data from 2015 in a south distinct in Shanghai were gathered from the spontaneous reporting system and analyzed. The general information, cause of errors, severity, primary diseases, involved system and organs, symptoms, and suspected drugs were investigated. A total of 1290 adverse drug events (ADEs), including 1079 ADRs and 211 MEcs (MEs causing ADE), were reported. Older patients suffered from both ADRs and MEcs (age distribution and dosage form were different between ADRs and MEcs). The main causes of errors were inappropriate usage and dosage of drugs and inappropriate indication selection. Most ADR and MEc cases were mild; the possibility of developing a severe adverse event was quite low. The distribution of the top 10 system and organs, and symptoms involved was significantly different between ADRs and MEcs, with J01 drugs (antibacterials for systemic use) being the leading cause in both. Our results suggested that a direct analysis of data from the spontaneous reporting system is a reliable, and convenient method to investigate MEs and ADRs, despite the existing limitations, and contributes to further understanding the current situation of MEs and ADRs in China.